Ki‐67 and MCM6 labeling indices are correlated with overall survival in anaplastic oligodendroglioma, IDH1‐mutant and 1p/19q‐codeleted: a multicenter study from the French POLA network. (10th October 2019) - Pouget, Celso; Hergalant, Sébastien; Lardenois, Emilie; Lacomme, Stéphanie; Houlgatte, Rémi; Carpentier, Catherine; Dehais, Caroline; Rech, Fabien; Taillandier, Luc; Sanson, Marc; Appay, Romain; Colin, Carole; et al.
Abstract: Anaplastic oligodendroglioma (AO), IDH‐mutant and 1p/19q codeleted (IDHmut+/1p19qcodel), is a high‐grade glioma with only limited prognostic markers. The primary objective of this study was to evaluate, by immunohistochemistry, the prognostic value of two proliferation markers, MCM6 and Ki‐67, in a large series of IDHmut+/1p19qcodel AO included in the POLA ("Prise en charge des Oligodendrogliomes Anaplasiques") French national multicenter network. We additionally examined the transcriptome obtained from this series to understand the functional pathways dysregulated with the mRNA overexpression of these two markers. The labeling indices (LI) of MCM6 and Ki‐67 were obtained via computer‐assisted color image analyses on immunostained AO tissues of the cohort (n = 220). Furthermore, a subgroup of AO (n = 68/220) was used to perform transcriptomic analyses. A high LI of either MCM6 (≥50%) or Ki‐67 (≥15%) correlated with shorter overall survival, both in univariate ( P = 0.013 and P = 0.004, respectively) and multivariate analyses ( P = 0.027; multivariate Cox model including age, mitotic index, MCM6 and Ki‐67). MCM6 and Ki‐67 LI also correlated with overall survival in an additional retrospective cohort of 30 grade II IDHmut+/1p19qcodel oligodendrogliomas. The prognostic value of MCM6 mRNA level was confirmed in The Cancer Genome Atlas (TCGA) IDHmut+/1p19qcodel gliomas. The transcriptomic approach revealed that high transcriptional expressions of MCM6 and MKI67 were both linked positively with cell cycle progression, DNA replication, mitosis, pro‐neural phenotype as well as neurogenesis, and negatively with microglial cell activation, immune response, positive regulation of myelination, oligodendrocyte development, beta‐amyloid binding and postsynaptic specialization. In conclusion, the overexpression of MCM6 and/or Ki‐67 is independently associated to shorter overall survival in IDHmut+/1p19qcodel AO. These two easy‐to‐use and cost‐effective markers could thus be used concurrently in routine pathology practice. Additionally, the transcriptomic analyses showed that AO with high proliferation index have down‐regulated immune response and lower microglial cells activation, and bears pro‐neural phenotype.